(untitled) (Nóema, 2014)
Using Virgil’s Aeneid VI as an example, this paper explores what might become of language and “truth” if contrary to Plato’s proposed course of education for the guardians of the state one moves, not up from sense perceptions to univocal, intelligible being, but down to the ambiguous realm of sleep, dreams and death.